Effects of Germination of Suaeda Salsa Seeds After Treating with Plant Hormones - XIANG Liang; CHEN Jiabo; WANG Yanjie; ZHAO Ying (Renmin Zhujiang)
In order to explore the key technical parameters of treating suaeda salsa seeds with plant hormone for rapid germination,and further enrich the method of rapidly recovering degraded coastal suaeda salsa wetland,this paper analyzes the effects of soaking suaeda salsa seeds in gibberellic acid (GA),indole acetic acid (IAA) and Kinetin (KT) solutions on the seed germination index by setting up different concentrations and treatment time in water culture experiment.The results show that:The optimal treatment conditions for the three plant hormones were 100 mg/L GA solution for 36 h,1.5 mg/L IAA solution for 12h,and 10 mg/L KT solution for 12 h respectively.Compared with the control,under the optimal pretreatment conditions of plant hormones,the germination percentage and germination rate of suaeda salsa seeds increased by 20.00% and 79.60%,17.65% and 136.84%,9.80% and 55.79%,respectively.Therefore,treating suaeda salsa seeds in GA,IAA and KT solutions under appropriate conditions can significantly increase their germination percentage and germination rate.